Pengelolaan Sarana Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Palangkaraya - Anang Rahman; Sardimi Sardimi (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
Facilities management is a crucial aspect in ensuring the quality of the learning process in higher education. This study aims to analyze facilities management at the Faculty of Teacher Training and Education (FKIP), Universitas Muhammadiyah Palangkaraya, focusing on three dimensions: planning, utilization, and maintenance. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation. Research subjects consisted of the Head of Administration Division, an administrative staff member, and a user representative, namely the Head of the Teacher Professional Education Program. Data validity was ensured through source and technique triangulation. The results show that facilities planning is carried out hierarchically through coordination between the faculty, the General Bureau, and the university, and is discussed in faculty academic meetings. An important finding of this study is the contribution of alumni as an alternative source for facilities procurement; however, this practice has not been supported by a written priority mechanism. Facilities utilization has been relatively effective through a two-session daily classroom scheduling system that prevents conflicts among study programs. Nevertheless, laboratory scheduling remains decentralized, and written standard operating procedures for facilities use are not yet comprehensive. In terms of maintenance, minor maintenance is handled responsively, while major damage still depends on the General Bureau, resulting in uncertain repair timelines. The main structural weaknesses are the absence of a dedicated maintenance budget at the faculty level and the lack of transparency in the asset disposal process. This study highlights the need to strengthen facilities governance through priority-based planning, written SOPs, and more structured maintenance budgeting